Initial performance and load analysis of the LowWind turbine in comparison with a conventional turbine. Issue 3 (September 2020) - Madsen, H Aa; Zahle, F; Meng, F; Barlas, T; Rasmussen, F; Rudolf, R T
Abstract: We present the preliminary design of a high capacity LowWind turbine rotor with a specific power of 100 W/ m 2, a rated power of 3.4MW and a 208m diameter rotor. The turbine is designed for optimal system integration and thus with a considerably increased power production at low to medium wind speed and stopped at 13 m/s. The AEP of the turbine, due to the large swept rotor area, is 40-45% higher than the AEP of a conventional on-shore turbine, the IEA Task 37 reference wind turbine with a 130 m diameter rotor and the same rated power of 3.4 MW. Initial aeroelastic simulations show that the loads of the LowWind turbine are generally higher than on the IEA turbine although comparable for some components at steady wind. For Design Load Case 1.2 (DLC1.2) for normal operation in turbulence we see a typical increase of around 20-40% of tower and rotor fatigue loads. However, this moderate increase for such big increase of rotor diameter is only obtained due to the highly flexible light weight rotor designed with a combination of peak shaving and blade bend twist coupling and for a low stop wind speed of 13 m/s.